Topical betamethasone and systemic colchicine for treatment of recurrent aphthous stomatitis: a randomised clinical trial - Surab Alsahaf; Khlood A. Alkurdi; Stephen J. Challacombe; Anwar R. Tappuni (BMC, 2023)
Abstract Background Recurrent Aphthous Stomatitis (RAS) is painful oral ulceration frequently treated with topical steroids. There is limited published evidence for the efficacy of any treatment for RAS and there remains a need for longitudinal randomised clinical trials to evaluate and compare the effectiveness of different therapies in the management of RAS. The aim of the current project was to assess the efficacy of betamethasone mouthwash and colchicine tablets, individually and combined, for the treatment of RAS, and to establish the optimum treatment period necessary for a significant reduction in the disease severity. Methodology A randomised, prospective, parallel-group clinical trial was conducted over one year, to compare the efficacy of three therapies in RAS. One hundred and six patients were randomized into three groups; 35 received betamethasone mouthwash, 35 had colchicine tablets and 36 received both therapies. The response was evaluated quantitatively every 3 months for 1 year, using the Ulcer Severity Score (USS). Results For all three treatment regimes, the mean USS decreased by about 30% in the first 3 months (p < 0.001). Further improvement was noted for up to 9 months. At the end of the study, the mean USS had improved by 50% from 34.9 ± 7.2 before treatment to 17.5 ± 8.9 after treatment (p < 0.001). Of included participants, 86% showed significant clinical improvement by the end of the study. There were no significant differences in outcomes between the three regimes (p < 0.05). Conclusions This clinical trial has provided evidence for the efficacy of betamethasone mouthwash and for colchicine tablets in the treatment of RAS and has shown that at least six months of treatment may be required for optimum effect. Clinical trial registration number: ISRCTN3267716. Date of clinical trial registration: 15/04/2018